The Contribution of TRPV4 Channels to Astrocyte Volume Regulation and Brain Edema Formation. (1st December 2018) - Pivonkova, Helena; Hermanova, Zuzana; Kirdajova, Denisa; Awadova, Thuraya; Malinsky, Jan; Valihrach, Lukas; Zucha, Daniel; Kubista, Mikael; Galisova, Andrea; Jirak, Daniel; Anderova, Miroslava
Highlights: TRPV4 channels play a protective role during ischemia-induced brain edema formation. Astroglial regulatory volume decrease in situ is not mediated by TRPV4 channels. The expression of TRPV4 channels in adult mouse astrocytes is very low. It does not influence the expression of other genes involved in volume regulation. Abstract: Transient receptor potential vanilloid type 4 (TRPV4) channels are involved in astrocyte volume regulation; however, only limited data exist about its mechanism in astrocytes in situ . We performed middle cerebral artery occlusion in adult mice, where we found twice larger edema 1 day after the insult in trpv4 −/− mice compared to the controls, which was quantified using magnetic resonance imaging. This result suggests disrupted volume regulation in the brain cells in trpv4 −/− mice leading to increased edema formation. The aim of our study was to elucidate whether TRPV4 channel-based volume regulation occurs in astrocytes in situ and whether the disrupted volume regulation in trpv4 −/− mice might lead to higher edema formation after brain ischemia. For our experiments, we used trpv4 −/− mice crossed with transgenic mice expressing enhanced green fluorescent protein (EGFP) under the control of the glial fibrillary acidic protein promoter, which leads to astrocyte visualization by EGFP expression. For quantification of astrocyte volume changes, we used two-dimensional (2D) and three-dimensional (3D) morphometrical approaches and a quantification algorithm based on fluorescence intensity changes during volume alterations induced by hypotonicity or by oxygen-glucose deprivation. In contrast to in vitro experiments, we found little evidence of the contribution of TRPV4 channels to volume regulation in astrocytes in situ in adult mice. Moreover, we only found a rare expression of TRPV4 channels in adult mouse astrocytes. Our data suggest that TRPV4 channels are not involved in astrocyte volume regulation in situ ; however, they play a protective role during the ischemia-induced brain edema formation.